PENERAPAN PATH ANALYSIS UNTUK MELIHAT PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN DAN CITRA RAWAT INAP KELAS III DI RSUD CUT NYAK DHIEN MEULABOH TAHUN 2012 - nurasmi Novrina (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2013)
Abstract The purpose of this research is analyzing the effect of service quality (Technical quality and Functional quality) to the satisfaction level and image to patient of third (III) class in Regional General Hospitals of Cut Nyak Dhien Meulaboh in 2012 by applying Path Analysis method. The results showed that the service quality variable as Technical quality dimensions directly affects to patients satisfaction (p=0.005). While the direct effect of Technical quality on image (p=0.001). Whereas the indirect effect of Technical quality on image through the satisfaction is 0.082 and the total effect is 0.602. The direct effect of service quality as Functional quality dimensions on patient satisfaction level (p=0.007), while the direct effect of Functional quality on image (p=0.46). Moreover the indirect effect of Functional quality on image through the satisfaction is 0.256 and the total effect is 1.044. Suggested to the management of Cut Nyak Dhien Meulaboh Regional General Hospital to provide a patient-need oriented quality of service. Improve further more Facilities and environmental health and also maintain and develop the existing facilities.